CBF/CBV maps in normal volunteers studied with (15)O PET: a possible index of cerebral perfusion pressure - Watabe, Tadashi (Neurosci Bull, 2014)
Local cerebral perfusion pressure (CPP) is a primary factor controlling cerebral circulation and previous studies have indicated that the ratio of cerebral blood flow (CBF) to cerebral blood volume (CBV) can be used as an index of the local CPP. In this study, we investigated whether the CBF/CBV ratio differs among different brain structures under physiological conditions, by means of (15)O positron emission tomography. Nine healthy volunteers (5 men and 4 women; mean age, 47.0 ± 1.2 years) were studied by H(2) (15)O bolus injection for CBF measurement and by C(15)O inhalation for CBV measurement. The CBF/CBV ratio maps were created by dividing the CBF images by the CBV images after anatomical normalization. Regions of interest were placed on the CBF/CBV maps and comparing the regions. The mean CBF/CBV ratio was highest in the cerebellum (19.3 ± 5.2/min), followed by the putamen (18.2 ± 3.9), pons (16.4 ± 4.6), thalamus (14.5 ± 3.3), cerebral cortices (13.2 ± 2.4), and centrum semiovale (11.5 ± 2.1). The cerebellum and putamen showed significantly higher CBF/CBV ratios than the cerebral cortices and centrum semiovale. We created maps of the CBF/CBV ratio in normal volunteers and demonstrated higher CBF/CBV ratios in the cerebellum and putamen than in the cerebral cortices and deep cerebral white matter. The CBF/CBV may reflect the local CPP and should be studied in hemodynamically compromised patients and in patients with risk factors for small-artery diseases of the brain.